Development Of Eunterprise Architecture Information System In Parungkuda Sukabumi Puskesmas District Using Togaf Adm Model - Moh Ival Alpian S; Cecep Warman (International Journal of Health Engineering and Technology, 2025)
This study aims to design an effective enterprise architecture for the information system of the Community Health Center in Parungkuda District, Sukabumi. Adopting the TOGAF (The Open Group Architecture Framework) and ADM (Architecture Development Method) Architecture Development Process Model, this study will provide systematic steps to design a structured and integrated architecture. Health services at the Community Health Center are one of the technical service units in the management of the Community Health Center. The Community Health Center is one of the government agencies engaged in the field of Health services in its daily life providing health services to the community. The Parungkuda Community Health Center has currently implemented a computer and information system to support its processes. Unfortunately, the availability of information systems as one of the health service facilities that are run is considered less than optimal. The purpose of this study is to design and implement the proposed information system which can later help optimize the health service management process at the Parungkuda Community Health Center. In this study, the TOGAF framework has been proposed as a reference for architectural design. Where TOGAF contains the structure and components of ADM (Architecture Development Method) which represents TOGAF itself and provides details on how to determine an enterprise architecture based on the main needs of the organization. The output produced in using this framework is a blueprint that is used as a reference for the Parungkuda Health Center itself to develop information system technology. Thus, every business process in the Parungkuda Health Center can answer all the visions and missions to be achieved. With the implementation of the health service information system, it is hoped that it can improve health services and efficiency, employees in manipulating service data at the Parungkuda Health Center.